PENERAPAN MODEL PEMBELAJARAN PARTISIFATIF AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN (PAKEM) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 70 BALAI MAKAM KECAMATAN MANDAU KABUPATEN BENGKALIS - Herlina Herlina; Syahrilfuddin Syahrilfuddin; Hamizi Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the problem of low student learning outcomes in science teaching fourth grade students of SDN 70 Balai Makam with an average grade of 60.92. The purpose of this research is to improve learning outcomes IPA fourth grade students of SD Negeri 70 Hall Tomb Mandau sub Bengkalis, through the application of participatory learning models, Active, Creative, Effective, and menyenagkan (PAKEM). This research is a classroom action research conducted in two cycles, one cycle will be done twice action research. As for the improvement of learning outcomes that have been conducted by Researchers in the first cycle and the second cycle in science lessons can be concluded, that the learning models of participatory, active, creative, effective, and menyenagkan (PAKEM) can improve learning outcomes IPA fourth grade students of SD Negeri 70 Balai Makam Mandau Bengkalis districts. This is evident from the increase is in the average student learning outcomes Increased 60.92 to 74.82 in the first cycle and a significant increase is in cycle II with an average of 87.85. This success is supported by the readiness of teachers in designing learning and the learning process is Carried out According to plan. Reviews These results indicate that the application of PAKEM learning models can improve learning outcomes IPA fourth grade students of SD Negeri 70 Balai Makam.Key Words: Learning Model PAKEM Learning Outcomes IPA